Self-Assembly of Integrin Ligands on the Apical Membrane Inhibits the Migration of Glioma Cells - Mang, Dingze (Langmuir : the ACS journal of surfaces and colloids, 2020)
Malignant brain cancer remains challenging in treatment due to the highly invasive quality of gliomas. Inspired by the upregulated expression of integrin β1 subunits in tumors, we designed and synthesized an integrin-targeting self-assembling ligand based on a laminin-derived peptide that selectively forms nanofibrous microdomains on the apical membrane of glioma cells, inhibiting their migration and invasion